2015
DOI: 10.1037/pspp0000023
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in activation of the parental care motivational system: Assessment, prediction, and implications.

Abstract: We report on the development, validation, and utility of a measure assessing individual differences in activation of the parental care motivational system: The Parental Care and Tenderness (PCAT) questionnaire. Results from 1,608 adults (including parents and nonparents) show that the 25-item PCAT measure has high internal consistency, high test-retest reliability, high construct validity, and unique predictive utility. Among parents, it predicted self-child identity overlap and caring child-rearing attitudes;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
155
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(165 citation statements)
references
References 95 publications
(153 reference statements)
10
155
0
Order By: Relevance
“…Faces of puppies were included as a condition in the study to test whether exposure to human infants uniquely influences social/ideological attitudes, or whether these attitudinal shifts may more broadly emerge from exposure to vulnerable non-human targets that may also elicit tenderness and affiliative motives. Prior research has suggested that cute and vulnerable animals may also activate caregiving motives [25] [26].Yet compared to parental care motives generated by human infants, these feelings produced by animals may be less likely to translate into types of social and intergroup vigilance examined in the present study. The threat of harm and exploitation from outgroup members may generally and automatically be expected to be directed at vulnerable human members of one's ingroup (such as infants), rather than animals or pets.…”
Section: Studymentioning
confidence: 62%
“…Faces of puppies were included as a condition in the study to test whether exposure to human infants uniquely influences social/ideological attitudes, or whether these attitudinal shifts may more broadly emerge from exposure to vulnerable non-human targets that may also elicit tenderness and affiliative motives. Prior research has suggested that cute and vulnerable animals may also activate caregiving motives [25] [26].Yet compared to parental care motives generated by human infants, these feelings produced by animals may be less likely to translate into types of social and intergroup vigilance examined in the present study. The threat of harm and exploitation from outgroup members may generally and automatically be expected to be directed at vulnerable human members of one's ingroup (such as infants), rather than animals or pets.…”
Section: Studymentioning
confidence: 62%
“…Supporting these predictions, tenderness is felt in response to human infants and also other baby‐like (i.e., cute and vulnerable) stimuli, including adults whose faces have been experimentally manipulated to appear more infantile (Buckels et al, ; Lishner et al, ; Lishner, Oceja, Stocks, & Zaspel, ), suggesting that tenderness is elicited via activation of the parenting motivational system. Like romantic love, parenting behaviors have been associated with increases in oxytocin (see Feldman, ), suggesting that experiences of tenderness may be associated with the mobilization of physiological resources that aid in parent–infant bonding (Lee, Macbeth, Pagani, & Young, ).…”
Section: Fundamental Motives and Associated Characteristic Emotionsmentioning
confidence: 93%
“…Kenrick et al () therefore contend that a fundamental parenting motivational system evolved in humans to help maximize the genetic interests of parents by ensuring that their offspring survive to reproductive age and are able to pass genetic material onto future generations. Tenderness, an emotion, which is psychologically distinct from empathy, sympathy, and romantic love (see Buckels et al, ; Kalawski, ; Lishner, Batson, & Huss, ; Weidman & Tracy, ), may have evolved to facilitate these adaptive needs by promoting a desire to nurture and care for vulnerable offspring (McDougall, ). If so, one's real or imagined offspring should activate the parenting motivational system and also elicit tenderness.…”
Section: Fundamental Motives and Associated Characteristic Emotionsmentioning
confidence: 99%
See 2 more Smart Citations